The Formation Of Iron Oxide Nanowires And Nanosheets By Thermal Oxidation Of Iron For Cr(Vi) Removal By Adsorption - Budiman, Faisal (2015)
Thermal oxidation of iron foil was done in dry air and water vapour at 400-800 oC to form α-Fe2O3 nanowires (NWs) and nanosheets (NSs) as adsorbent to remove Cr(VI) from aqueous solution. Oxidation parameters studied were the effect of surface pre-treatment, the effect of oxidation temperature, time and water vapour on the NWs or NSs formation. It appears that the increase of Fe roughness (by grinding) produced NWs and NSs uniformly covering the surface of the Fe metal with high areal density. Oxidation at different temperatures resulted in the formation of NWs at 400 and 800 oC while at 500 and 600 oC, NSs formed. At 700 oC, the surface oxide has coral-structure. Temperature 800 oC was acknowledged as the best oxidation temperature for high aspect ratio (27) NWs formation. Higher areal density NWs were formed when oxidation was done in water vapour due to the influence of proton from water dissociation. Different oxidation time at 800 oC in water vapour was conducted to investigate the growth of NWs. NWs started to form at 5 min but for high areal density 23 NWs/100 μm2 and aspect ratio of 27, oxidation must be done for 120 minutes. Mechanism of NWs formation was proposed to follow the stress-driven mechanism being the screw dislocations as the nucleation centres for the NWs formation. From HR-TEM, XRD and Raman spectroscopy, the NWs were found to be α-Fe2O3. Cr(VI) with concentration 200 mg/L was successfully adsorbed on the α-Fe2O3 NWs within 90 minutes, whereas on NSs, 112 mg/L was adsorbed. The kinetic and isothermal studies described the adsorption behavior of Cr(VI) on α-Fe2O3 to follow pseudo-second order and Langmuir’s model respectively. The adsorption capacity of α-Fe2O3 NWs is 61.57 mg/g. The main mechanism of Cr(VI) removal by the α-Fe2O3 NWs due to electrostatic reaction between negative chromate ions and positively charge of adsorbent.